2013
DOI: 10.1104/pp.113.215699
|View full text |Cite
|
Sign up to set email alerts
|

Modified Clp Protease Complex in the ClpP3 Null Mutant and Consequences for Chloroplast Development and Function in Arabidopsis      

Abstract: The plastid ClpPRT protease consists of two heptameric rings of ClpP1/ClpR1/ClpR2/ClpR3/ClpR4 (the R-ring) and ClpP3/ ClpP4/ClpP5/ClpP6 (the P-ring) and peripherally associated ClpT1/ClpT2 subunits. Here, we address the contributions of ClpP3 and ClpP4 to ClpPRT core organization and function in Arabidopsis (Arabidopsis thaliana). ClpP4 is strictly required for embryogenesis, similar to ClpP5. In contrast, loss of ClpP3 (clpp3-1) leads to arrest at the hypocotyl stage; this developmental arrest can be removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 87 publications
6
73
1
Order By: Relevance
“…Moreover, chloroplast-encoded proteins were clearly not affected in the same manner (e.g., ribosomal proteins levels are barely changed while thylakoid proteins are strongly downregulated), suggesting that despite the strong increase in protein translation factors and tRNA synthases, plastid gene expression was not systematically affected. Direct comparison of the significantly changed plastid proteins with significantly changed chloroplast proteins in CLPPR core and CLPC1 mutants Kim et al, 2009Kim et al, , 2013Zybailov et al, 2009;Nishimura et al, 2013) showed great consistency as is illustrated in Table 1. This suggests that the clpt1-2 clpt2-1 molecular phenotype results mainly from reduced Clp protease capacity (see Discussion).…”
Section: No Differential Effect On Chloroplast-encoded Compared With mentioning
confidence: 81%
“…Moreover, chloroplast-encoded proteins were clearly not affected in the same manner (e.g., ribosomal proteins levels are barely changed while thylakoid proteins are strongly downregulated), suggesting that despite the strong increase in protein translation factors and tRNA synthases, plastid gene expression was not systematically affected. Direct comparison of the significantly changed plastid proteins with significantly changed chloroplast proteins in CLPPR core and CLPC1 mutants Kim et al, 2009Kim et al, , 2013Zybailov et al, 2009;Nishimura et al, 2013) showed great consistency as is illustrated in Table 1. This suggests that the clpt1-2 clpt2-1 molecular phenotype results mainly from reduced Clp protease capacity (see Discussion).…”
Section: No Differential Effect On Chloroplast-encoded Compared With mentioning
confidence: 81%
“…These accessions can therefore be utilized as conditional triple knockouts to study the functions of three intriguing chloroplast proteins and their associated complexes. Based on the known lethality of Arabidopsis mutants defective in ClpP subunits (Kim et al, 2013), the presumed lethality of tobacco (Nicotiana tabacum) cells harboring plastid clpP1 gene disruptions (Kuroda and Maliga, 2003), and the viability of white leaf sectors in the maize (Zea mays) iojap mutant, which lack ClpP1 because they are devoid of chloroplast ribosomes (Walbot and Coe, 1979), we postulate that ClpP1 functions primarily to modulate chloroplast translation. This model predicts that in our system, where chloroplast translation is blocked through exposure to spectinomycin or mutations that disrupt chloroplast ribosomes, loss of ClpP1 activity should not further limit the growth of cells already defective in chloroplast translation.…”
Section: Loss Of Tic20-iv-mediated Chloroplast Protein Import Resultsmentioning
confidence: 99%
“…The first approach identified four candidate genes that seemed to explain the importance of chloroplast translation: accD (Kode et al, 2005); ycf1 (Drescher et al, 2000), which functions in protein import (Kikuchi et al, 2013); ycf2 (Drescher et al, 2000), whose function remains unknown; and clpP1 (Kuroda and Maliga, 2003), which encodes part of the ClpP protease that regulates protein degradation (Kim et al, 2013). All four genes are retained in the plastids of most flowering plants, consistent with their proposed essential functions.…”
Section: Comparative Genomics and The Loss Of Essential Chloroplast Gmentioning
confidence: 94%